Utilizing Cotton Bud Sticks as a Sustainable Sound Absorber - Norazmi, Anees Arisha; Samsudin, Emedya Murniwaty (Recent Trends in Civil Engineering and Built Environment, 2021)
Sustainable products, such as recycled material, may also be deemed a renewable substitute due to a lower level of waste generation and raw material dependency. Cotton buds plastic stick should be placed in the dustbin after being used, but several are flushed down the toilet and then enter the beaches through the sewage pipe. Such problems offer an incentive for recycled material, which is a cotton bud plastic sticks to be reused and produced as a substitute material for sound absorption. This study focuses on the comparison of sound absorption performance of cotton bud sticks with and without the cotton layer in different thickness. This study involves sound absorption of cotton bud sticks on the low and high-frequency region using Impedance Tube following ISO 10534-2 (2001). The cotton bud sticks was cut into 2 cm and 3 cm thickness. The cotton bud sticks handled in 4 conditions for every thickness, which is cotton bud sticks without cotton layer, with cotton layer at front, with cotton layer at the back, and cotton layer at the front and back of the sample. For sample 3 cm thickness with cotton at the front, the highest sound absorption coefficients of 0.902 is obtained at high frequency area and the optimum frequency is 3150 Hz. This indicates that the sound absorption for samples with cotton has a high-frequency range than the sample without the cotton layer. The findings revealed that by adding fibrous material (cotton layer) at the front surface of sample, improvements in sound absorption coefficients of cotton bud sticks are achieved. Therefore, cotton bud sticks covered with cotton layer has the potential to become one of the sound absorption materials for high frequency region for acoustics used.